Constituintes sangüíneos de bovinos lactantes, desmamados e adultos das raças Nelore (Bos indicus) e Holandesa (Bas taurus) e de bubalinos (Bubalus bubalis) da raça Murrah - Fagliari, J. J. [UNESP]; Santana, A. E. [UNESP]; Lucas, F. A. [UNESP]; Campos Filho, E. [UNESP]; Curi, P. R. [UNESP] (My University, 1998)
Blood samples from lactating, weaned and adult Holstein-Fresiean and Nelore cattle and Murrah buffaloes were tested through the study of hemogram and serum constituents. Red cell and leukocyte counts, and blood pH, fibrinogen, glucose, calcium, and phosphorus levels were similar in cattle and buffalo. Total protein, urea, creatinine, hemoglobin, magnesium, iron and aspartato aminotransferase and alanine aminotransferase activities were higher in buffalo than cattle. Leukocyte counts were higher for weaned Holstein cattle than for Nelore cattle but similar to buffalo and Nelore cattle had the lowest neutrophil counts. Bilirrubin levels were lower for buffalo than for cattle. Phosphatase alkalyne activities were lower for weaned buffalo than for other animals. Gammaglutamyltransferase activities were the highest for lactating and weaned buffalo.
Blood constituents of lactating, weaned and adult Nelore cattle (Bos indicus), and Holstein cattle (Bos taurus), and Murrah buffalo (Bubalus bubalis)
Keywords: Blood constituent; Buffalo; Cattle